International Legal Regulation of the Children’s Rights - KAPSALYAMOV, Kairat; KAPSALYAMOVA, Saule; OSMANOVA, Dinara; ZHUZBAEV, Baurzhan; ZHUSIPOVA, Bakhyt (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019DO - 10.14505/jarle.v10.7(45).08, 2019)
This research discusses the urgent problems of regulating children’s rights at the global level. The goal is a comprehensive theoretical analysis of the children’s rights and their normative consolidation in international law; studying the effectiveness of protection mechanisms and the development of theoretical and practical proposals directed to improving the measures taken by Kazakhstan in this direction. The methodological basis of the study forms historical and comparative legal methods, which involved the analysis of scientific works on the issues of sociology, psychology, economics and law. At the same time, research methods include logical and systematic analyzes. The primary sources of information were laws and regulations defining the development aspects of the institution responsible for protecting the rights of children. Analyzing the situation in Kazakhstan showed that there are sufficient issues to be addressed. For instance, it is necessary to ensure that all children have the right to receiving high-quality educational services such as preschool organizations. Moreover, the existing ones should be modernized, and their total number should be increased. In villages, it is necessary to establish ungraded schools according to the desire of the people. The research results can be applied in the legal education system in studying the children’s rights; as well as in professional legal and pedagogical educational institutions, in the study of subjects such as ‘Human Rights’ and ‘Children's Rights’.